Adsorption and Removal of Thymol from Water Using a Zeolite Imidazolate Framework-8 Nanomaterial. (4th March 2021) - Ganta, Deepak; Guzman, Carlos; Combrink, Keith; Fuentes, Mario
Abstract: The purpose of this work is to address the limitations in the adsorption capacity of existing materials for the removal of thymol from water. A porous zeolite imidazolate framework-8 (ZIF-8) nanomaterial with a very high surface area was used to adsorb and remove thymol from water. The pH of the solution was maintained at 6.1 to improve the adsorption capacity. The thymol adsorption capacity is reported as a function of the pH, initial concentration, and contact time. The experimental adsorption measurements at equilibrium fitted well with both Langmuir and Freundlich isotherm models. The maximum adsorption capacity of thymol on ZIF-8 was determined to be 454.6 mg/g using the Langmuir model. Furthermore, the adsorption kinetics were investigated and the results were in agreement with a pseudo-first-order kinetic model.